Cutaneous Fungal Infection With Alternaria in a Patient With Myelodysplastic Syndrome: Successful Treatment With Topical Silver Chloride Gel. Issue 2 (March 2016) - O'Meara, Conor; Boyanton, Bobby L.; Spurlin, David; Carpenter, Christopher F.
Abstract : Abstract: We report a case of cutaneous alternariosis in an 80-year-old man with myelodysplastic syndrome. He developed a small slippery mobile mass in the proximal right middle finger. After excision, the mass revealed suppurative and granulomatous inflammation with negative special stains, possibly representing a ruptured epidermoid cyst or follicle. The biopsy wound did not heal, despite application of antibiotic ointment. Repeat biopsy findings suggested an infectious etiology; special stains were again negative, and the tissue was not sent for culture. The wound persisted, and subsequent deeper biopsy with culture eventually identified Alternaria species as a pathogen. By the time the Alternaria was identified, the patient, on his own initiative, had begun applying a topical over-the-counter silver chloride gel, with significant improvement in the wound. He was advised to continue its application, and within 3 months his wound had completely healed.